The Severity of Depression, Anxiety, and Stress: Recommendations From Joint Work of Research Center and Psychology Clinics in COVID-19 Pandemic - Shahid, Hira; Hasan, Muhammad Abul; Ejaz, Osama; Khan, Hashim Raza; Idrees, Muhammad; Ashraf, Mishal; Aftab, Sobia; Qazi, Saad Ahmed (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic has significantly affected the psychological stability of general population of Pakistan. However, research on the severity of COVID-19 induced depression, anxiety, and stress (DAS) in Pakistan is scarce. This paper thereby investigates the severity of COVID-19 induced DAS based on demographic, socioeconomic, and personal feeling variables by modelling DAS. Snowball sampling strategy was adopted to conduct online survey from 03-July to 09-July 2021. Out of 2442, 2069 responses from Karachi were included. Descriptive and inferential statistics (binary and multinomial logistic regression analysis) were performed using SPSS V21 (IBM, 2013) to identify significant determinants and their association with DAS severity. The result of this study indicates 27.8%, 21.7%, and 18.3% respondents suffer from severe and extremely severe states of depression, anxiety and stress respectively. Binary logistic regression revealed that, age is a significant determinant with odds of having 4.72 (95% CI = 1.86–11.97), and 5.86 (95% CI = 2.26–15.2) times greater depression, and stress for respondents aged 19-26 years. Moreover, gender-based difference is also observed with females 1.34 (95% CI = 1.08–1.68) and 1.75 (95% CI = 1.40–2.20) times more likely to exhibit anxiety and stress than males. Furthermore, marital status is significant determinant of depression with odds of having depression is 0.67 (95% CI = 0.48–0.93) times greater for married population. Multinomial logistic regression revealed that those who believe COVID-19 pandemic has affected them mentally, fear new COVID-19 cases and deaths, depressed due to imposition of lockdown, believe they will not survive COVID-19 infection and spend more time on social media gathering COVID-19 updates suffer from extremely severe state of depression (ORmental-effect-of-pandemic = 3.70, ORnew-COVID-19-cases-and-deaths = 2.20, ORimposition-of-lockdown = 17.77, ORsurvival-probability = 8.17, ORtime-on-social-media = 9.01), anxiety (ORmental-effect-of-pandemic = 4.78, ORnew-COVID-19-cases-and-deaths = 3.52, ORimposition-of-lockdown = 5.06, ORsurvival-probability = 8.86, ORtime-on-social-media = 5.12) and stress (ORmental-effect-of-pandemic = 6.07, ORimposition-of-lockdown = 11.38, ORsurvival-probability = 15.66, ORtime-on-social-media = 4.39). Information regarding DAS severity will serve as a platform for research centers, and psychological clinics, to work collectively and provide technology-based treatment to reduce the burden on the limited number of psychologist and psychotherapist.